Hugh Chisholm papers - Chisholm, Hugh, 1913-1972.
Chiefly writings, including poetry, essays, articles, and book proposals, together with correspondence, family papers, financial notes, clippings, wedding album, and photographs. Correspondents include Rolf Andreson, John Hersey, and Henry Miller.
Poet, translator, and editor for the Bollingen Foundation. Full name: Hugh Joseph Chisholm.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andreson, Rolf -- Correspondence; Hersey, John, -- 1914-1993 -- Correspondence; Miller, Henry, -- 1891-1980 -- Correspondence; Chisholm family; Bollingen Foundation; American poetry -- 20th century; Editors; Editors; Poets